Analysis of medicinally important compounds and anti-oxidant activity in solvent extracts of coriander (Coriandrum sativum L.) plant parts - R Saxena, L K Sharma, J K Ranjan, S N Saxena, S S Rathore, G Maheshwari, (Journal of Spices and Aromatic Crops, 2016)
Total phenolic, flavonoid content and antioxidant activity of crude extract of seeds, roots, stem and leaves of coriander plant were determined. Maximum phenolic content (62.6 and 50.141 mg gallic acid equivalents (GAE) g-1 extract) was observed in distilled water extract of fresh and dried roots followed by methanol extract (49.53 and 47.32 mg in green and dried stem respectively). Ethyl acetate extract showed more phenolics in dried stem (12.734 mg GAE g-1 extract) and leaves (8.62 mg GAE g-1 extract) as compared to green stem and leaves (1.808 and 5.433 mg, respectively). Distribution of flavonoids content in different green as well as dried plant parts and different solvents showed less variation in phenolic and flavonoid contents which ranged from a maximum of 9.843 mg quercetin equivalents (QE) g-1 extract in green seeds to a minimum of 4.40 mg in green stem. 1, 1-Diphenyl-2-picrylhydrazin scavenging as a measure of antioxidant capacity was more in distilled water extract of green stem (94.49%) followed by methanol crude extract (76.256%) and ethyl acetate extract (59.706%).